(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Our objective is to show the weakness of the recent thermodynamics of chemical reactions. We show that such a thermodynamic theory of chemical reactions, which could be similar to the generalized Onsagers theory in thermodynamics, is not reality at the moment.